Strengthening MSME Capacity through the Development of Simple Financial Recording in Parepare City - Yasri Tarawiru; Fajar Ladung; Edy Susanto; Jusnaeni (Publikasi Inspirasi Indonesia, 2026)
This study aims to analyze the development of simple financial recording practices among Micro, Small, and Medium Enterprises (MSMEs) in Parepare City, focusing on the validity, reliability, and determinants of their implementation. Using a descriptive quantitative approach, data were collected from 30 MSME respondents through a structured questionnaire covering three main variable dimensions: basic accounting knowledge (X1), financial management behavior (X2), and financial recording implementation (Y). Validity testing using Pearson Correlation revealed that all instrument items are valid, with r-values significantly above the critical value at the 0.01 level. Reliability analysis using Cronbach's Alpha yielded coefficients of 0.791 for X1 (10 items), 0.808 for X2 (7 items), and 0.816 for Y (6 items), all exceeding the 0.70 threshold. Multiple regression analysis demonstrates that both basic accounting knowledge and financial management behavior significantly and positively influence MSME financial recording implementation (R² = 0.960; F = 321.202; p < 0.001). Partial testing indicates that X1 exerts a stronger influence (β = 0.374; t = 4.284; p < 0.001) compared to X2 (β = 0.310; t = 2.591; p = 0.015). Normality testing using the Kolmogorov-Smirnov method confirms residual normality (p = 0.200 > 0.05). These findings suggest that capacity-building programs focusing on basic accounting literacy and financial management behavior are critical pathways to improving MSME financial governance in Parepare